Assessment of the river flow regimes over the Chitral and Gilgit Basins, Pakistan, under IPCC climate change scenarios using the HyMoLAP-SM model. Issue 11 (14th October 2022) - Hassan, Syed Ahmad; Khan, Mehwish Shafi
Abstract: Modelling the river flow process during uncertain climatic conditions is a challenging task. This paper attempts to apply the hydrological model based on the least action principle (HyMoLAP) at Chitral and Gilgit stations with few modifications. The topographic wetness index, the concept of degree-day factor and snowmelt (SM) using the snow cover area (SCA) have been incorporated into the improved HyMoLAP-SM structure. It is found that the HyMoLAP-SM model significantly enhanced the accuracy of the river flow estimation and forecast. Furthermore, the model seems highly sensitive to the choice of nonlinearity parameter and moderately sensitive to SM coefficients. Moreover, the response of river flow to climate change scenarios has been projected by utilizing modelled outcomes under temperature and precipitation variations. Overall, the results suggest that average river flow may get increased (reduced) by about 60% (40%) by the increase (decrease) in temperature. On the other hand, an increase (decrease) in precipitation at Chitral (Gilgit) may increase (decrease) the average flow by about 27% (200%) [19% (8%)] at the respective station. These results may be utilized for future flood/agricultural planning in Pakistan. Additionally, results obtained in this study may not be applicable to other geographical regions or interchangeable with other modelling purpose. HIGHLIGHTS: The HyMoLAP-SM model is highly sensitive (moderately sensitive) to the choice of nonlinearity (snowmelt) parameters. The response of river flow to the change in temperature values seems to be steady at both the stations. The response of river flow to the increasing precipitation scenario is likely to be chaotic at the Gilgit station. HyMoLAP-SM may capture the physical composition of the river flow adequately. Graphical Abstract